Development of an environmental management novel program in watersheds to improve water quality in rivers in the Reserva Forestal Golfo Dulce in Península of Osa, Costa Rica - Calvo-Brenes, Guillermo (2016)
Processes that lead to a sustainable development should include economical, social and cultural development. Water use is the best indicator of economical and social development of a country. Research done in the past shows the relationship between water quality and environmental variables.In the Peninsula of Osa, the Conservation Area National System (SINAC) has begun a land acquisition processes inside the Golfo Dulcet Forestall Reserve (RFGD) from private landowners without having clear buying policies and not knowing the impact in water quality the different use land has on it.The project objective was to elaborate an environment protection program based on land acquisition policies focus on the protection or improving oh water quality.The use of a water quality prediction tool based on environment variables was key to evaluate the effect of environmental changes in water quality, through the analysis of different scenarios in the area selected.It was found that land use for pasture or chaparral does not negatively affect the water quality. All the contrary occurs when land use is agricultural. The conclusion is that SINAC has to increase the land buying program inside the RFGD to be used for forest, ideally, to overcome possible extensive use of land in agricultural activities along the coastal area, where SINAC has no control.